Functions of declarative and interrogative sentences in popular scientific texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article focuses on the functional impact of declarative and interrogative sentences on popular scientific texts. The main function of above mentioned units imitates the dialogue between the author and the reader. As a result drawing reader’s attention a certain feedback to the reader is created and author’s communicative purpose to control the reader’s thought is achieved. Amplification of interrogative sentences enhances the expressiveness of the popular scientific text and emotionally influences on the reader.This research confirms the idea that the declarative and interrogative sentences can also perform the problem function in the text, which is usually presented by means of interrogative sentences. This feature of interrogative sentences to mark a new theme in a popular scientific text allows the reader to predict more accurately the disclosure of the topic and provides adequate and full understanding of the content. This paper demonstrates that declarative and interrogative sentences are mostly used in such paragraphs of the texts which contain conceptually meaningful information, as well as parts that reveal considering and thinking about unresolved problems.
Keywords: declarative and interrogative sentences; dialogue; popular scientific text; dialogue imitating function; problem function; definition function